2016
DOI: 10.1038/aps.2016.91
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylisovaltratum disrupts microtubule dynamics and causes G2/M-phase arrest in human gastric cancer cells in vitro

Abstract: Aim:Deacetylisovaltratum (DI) is isolated from the traditional Chinese herbal medicine Patrinia heterophylla Bunge, which exhibits anti-cancer activity. Here, we investigated the effects of DI on human gastric carcinoma cell lines in vitro and elucidated its anti-cancer mechanisms.Methods:Human gastric carcinoma AGS and HGC-27 cell lines were treated with DI, and cell viability was detected with MTT assay. Cell cycle stages, apoptosis and mitochondrial membrane potential were measured using flow cytometry. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…MELK is an oncogenic kinase essential for early recurrence of hepatocellular carcinoma (Xia et al, 2016). Studies have shown that MELK is a novel biomarker and a potential therapeutic target in cervical cancer (Lv et al, 2018), triple-negative breast cancer (Moreno, 2016) and gastric cancer (Zhang et al, 2016a). NDC80 (Nuclear division cycle 80) is also known as highly expressed in cancer 1 (HEC1).…”
Section: Discussionmentioning
confidence: 99%
“…MELK is an oncogenic kinase essential for early recurrence of hepatocellular carcinoma (Xia et al, 2016). Studies have shown that MELK is a novel biomarker and a potential therapeutic target in cervical cancer (Lv et al, 2018), triple-negative breast cancer (Moreno, 2016) and gastric cancer (Zhang et al, 2016a). NDC80 (Nuclear division cycle 80) is also known as highly expressed in cancer 1 (HEC1).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular function analysis revealed that genes in the blue module were enriched for the tubulin binding, microtubule binding, and microtubule motor activity pathways. Disrupted microtubule dynamics have previously been reported to modulate cell proliferation in several human tumors, including hepatocellular carcinoma (HCC) (Zhang et al, 2016;Aboubakr et al, 2017). The cellular component analysis revealed that genes in the blue module were predominantly associated with spindle, kinetochore, and mitotic spindle cellular components, which serve essential functions during mitosis (Sharp et al, 2000).…”
Section: Categorymentioning
confidence: 99%
“…Deacetylisovaltratum, extracted from Patrinia heterophylla Bunge. (Caprifoliaceae, was treated to AGS and HGC-27 human gastric cancer cell lines for 24 h at the dose of 4, 8, 16 μM/mL and 10, 20, 30 μM/mL, respectively [60]. Deacetylisovaltratum induced mitochondrial and caspase-dependent apoptosis.…”
Section: Apoptosis-inducing Natural Molecules In Gastric Cancermentioning
confidence: 99%
“…(Gentianaceae) induced S phase cell cycle arrest [39,40,77,82]. Deacetylisovaltratum, Euphorbia lunulate (Euphorbiaceae) extract, phloretin, trifolirhizin, and tanshinone IIA triggered G2/M phase cell cycle arrest [44,46,55,60,76]. Jinlong Capsule halted the cell cycle in S and G2/M phase [89].…”
Section: Role Of Natural Products To Arrest Cell Cycle In Gastric Cancermentioning
confidence: 99%